Організація розвивального освітнього середовища початкової школи України (1990-ті рр.) - Смолюк, Світлана; Smoliuk, Svetlana (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті здійснено аналіз провідних ідей щодо формування розвивального освітнього середовища в початковій школі України у 90-х роках ХХ сторіччя. Окреслений період автор розглядає як початок демократичних перетворень в Україні, що викликало сплеск педагогічної ініціативи, відродження народних традицій навчання, виховання та розвитку учнів. Наголошується на проблемах соціокультурного становлення зростаючої особистості, гуманізації та гуманітаризації початкової освіти.The article analyzes the leading ideas on the formation of developing the educational environment in elementary school Ukraine in the 90-es years of the XX century. Based on the study and analysis of archival materials on primary education late XX century shows that in 1970-1980 years of the formation of educational environment occurred in the conditions of implementation of an integrated approach to learning. Outlined during the author sees as the beginning of democratic changes in Ukraine, which caused a surge in educational initiatives revival of folk traditions of training, education and development of students. Emphasized on socio-cultural issues becoming increasingly individual, humanization and humanization of primary education. So real practical possibilities for designing educational developmental environment of elementary school significantly increased with the intensification of information and communication technologies and concepts in terms of man-yevrointeґruvannya, especially in the XX century.
developing educational environment Ukraine elementary school (1990-es years)
Keywords: початкова школа; розвивальне освітнє середовище; гуманізація освіти; primary school; developmental educational environment; humanization of education